The protection in olive orchards: set up of technical assistance and phytosanitary appraisal [printed version also available in Arabic] - Barrani A.; Hallak H.; Nus B.E.; Bashi A.; Najm K.; Abdallah Y.; Contento F.; Dubla E.; Guario A.; Cardone G.L. (Syrian national strategic plan for olive oil quality : final report, 2007)
During the implementation of the Program Technical assistance for the improvement of olive oil quality in Syria, a specific activity has been focusing on IPM strategies and organic production first appraisals in 4 main oil producing regions providing the 72,20 percent of the national olive oil production. 12 demonstration plots have been established and intensive training of 3 local trainees to act as responsible for the different domains has been delivered both in Syria (92 days/man) and in Italy (111 days /man). Those first trials on main key pests and diseases affecting the olive tree in Syria (P. oleae, B. oleae, P. unionalis, Z. pyrina, S. oleagina) have been provided over 2 years, 2005 and 2006 and they represent a good base for further indications. Nowadays, Syria is the first country in the area which has available a tested model of a regional phytosanitary bulletin, an IPM and biotechnical calendar, trained engineers at GCSAR Olive Dept. of Idleb as very skilled professionals at institutional level already in connection with international experts of the sector through a LAN with ADSL internet connection. All the related activities have involved both the Public extension (Min. of Agriculture) and farmers. Raising awareness on olive oil quality and sensibilization of the whole stakeholder (2.300 participants in 2 years) has been intensively done during the implementation phase. It is now necessary to take a further step in order to foster networking activities, to link information gathering among the different oil producing regions, with a particular focus on the accurate involvement of selected personnel at the Min. of Agriculture level. This Olive IPM national network can be considered a feasible step looking forward to ensure the necessary improvement of the olive oil quality in Syria.